Comparative Whole-Genome Analysis of Neisseria gonorrhoeae Isolates Revealed Changes in the Gonococcal Genetic Island and Specific Genes as a Link to Antimicrobial Resistance - Shaskolskiy, Boris; Kravtsov, Dmitry; Kandinov, Ilya; Gorshkova, Sofya; Kubanov, Alexey; Solomka, Victoria; Deryabin, Dmitry; Dementieva, Ekaterina; Gryadunov, Dmitry (Frontiers in Cellular and Infection Microbiology, 2022)
Comparative whole-genome analysis was performed for Neisseria gonorrhoeae isolates belonging to the Neisseria gonorrhoeae multiantigen sequence typing (NG-MAST) types predominant worldwide — 225, 1407, 2400, 2992, and 4186 — and to genogroup 807, the most common genogroup in the Russian Federation. Here, for the first time, the complete genomes of 25 N. gonorrhoeae isolates from genogroup 807 were obtained. For NG-MAST types 225, 1407, 2400, 2992, and 4186, genomes from the Pathogenwatch database were used. The phylogenetic network constructed for 150 genomes showed that the clustering according to NG-MAST type corresponded to the clustering according to genome. Comparisons of genomes of the six sequence types revealed 8-20 genes specific to each sequence type, including the loci for phase variations and genetic components of the gonococcal genetic island (GGI). NG-MAST type 2992 and 4186 isolates either lacked the GGI or carried critical mutations in genes essential for DNA secretion. In all analyzed genogroup 807 isolates, substitution of the essential atlA gene with the eppA gene was found, accompanied by a change in the traG allele, replacement of the ych gene with ych1, and the absence of the exp1 gene, which is likely to result in loss of GGI functionality. For the NG-MAST type 225, 1407 and 2400 isolates, no premature stop codons or reading frameshifts were found in the genes essential for GGI function. A relationship between isolate susceptibility to ciprofloxacin, penicillin, tetracycline and the presence of lesions in GGI genes necessary for DNA secretion was established. The N. gonorrhoeae evolutionary pathways, which allow a particular sequence type to maintain long-term predominance in the population, may include changes in genes responsible for adhesion and virulence, changes in the GGI structure, preservation of genes carrying drug resistance determinants, and changes in genes associated with host adaptation or encoding enzymes of biochemical pathways.